Event Marketing Strategy in Increasing Brand Awareness - Suryana, Popo (Jurnal Ekonomi, Akuntasi dan manajemen Indonesia (JEAMI), 2022)
Brand awareness is a key element in the successful marketing of a product or service. Event marketing is considered a potential method to achieve these goals, involving consumers directly through experiences and interactions. This research aims to explore and analyze marketing strategies through event marketing as an effort to increase brand awareness. This research uses a qualitative approach with descriptive methods. The results of research on event marketing strategies with a focus on increasing brand awareness show that a holistic and sustainable approach provides a significant positive impact. By choosing the right type of event, creating a memorable experience, and utilizing social media effectively before, during, and post-event, companies can achieve their marketing goals. The research results also highlight the importance of providing quality merchandise and attractive prizes to participants as a form of appreciation, as well as maintaining active communication to strengthen ties with them. With this strategy, research shows that companies can build strong brand awareness, expand their customer base, and build sustainable relationships with consumers.